Pemetaan Budaya Organisasi pada Perusahaan Keluarga Menggunakan OCAI (Organizational Culture Assesment Instrument) - Freddy Aldo Setiawan; Suhaji Suhaji (Jurnal Ilmiah Aset, 2019)
The purpose of this research is to know the organizational culture profile in a company in current situation, and preferred culture. The object of this research is a family company named CV. Mitra Sejahtera which located at Rembang and Lamongan. The samples size of this research are 72 respondens with census technique in sampling method. Organizational Culture Assessment Instrument is used to mapping an organizational culture in this research. OCAI is measured with dimensions: dominant characteristic, organizational leadership, management of employees, organizational glue, strategic emphases and criteria of success. The result of this research is for the current situation, the strong culture are clan culture with mean score 32,60 and hierarchy culture with mean score 30,21. For preferred culture, the strongest culture preferred are hierarchy culture with mean score 34,17 and clan culture with mean score 32.03.